2016
DOI: 10.33549/physiolres.933214
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Continuous Passive Motion Initiated After the Onset of Arthritis on Inflammation and Secondary Hyperalgesia in Rats

Abstract: This study investigated the effect of continuous passive motion (CPM) initiated after the onset of arthritis in rats. Rats were injected with 3 % kaolin/carrageenan in the knee joint and randomized to the control, immobilization (IM), or CPM group. The knee joints of the IM and CPM groups were immobilized with a cast for 56 days. In the CPM group, CPM exercise was administered for 60 min/day (6 times/week). Joint transverse diameter and pressure pain threshold (PPT) were assessed as indicators of inflammation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 30 publications
0
9
0
1
Order By: Relevance
“…Also, since shoulder joint pain evaluation in a shoulder joint disease model has been reported to be most feasible at C5, we focused on the C5 spinal dorsal horn [ 19 , 20 ]. As investigated items, pain and CGRP, which has been used in the evaluation of central sensitization in spinal dorsal horn inflammation [ 25 , 26 , 27 ], were applied. In addition, in the intraarticular study TSG-6, which is an anti-inflammatory factor secreted by MSC, was measured [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Also, since shoulder joint pain evaluation in a shoulder joint disease model has been reported to be most feasible at C5, we focused on the C5 spinal dorsal horn [ 19 , 20 ]. As investigated items, pain and CGRP, which has been used in the evaluation of central sensitization in spinal dorsal horn inflammation [ 25 , 26 , 27 ], were applied. In addition, in the intraarticular study TSG-6, which is an anti-inflammatory factor secreted by MSC, was measured [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The plaster cast was replaced at least every 3 days to prevent loosening and edema in the hind limb. The rats were able to move freely in the cage by using the three limbs that were not immobilized [24,25].…”
Section: Methods Of Immobilizationmentioning
confidence: 99%
“…Apart from this, this study showed that CPM significantly decreased the patients' level of pain which was consistent to other findings [ 11 , 12 ]. The reasons might be a decreased inflammation and mitigated hyperalgesia [ 36 – 39 ]. The improvement in the CPM group from 6 weeks to 6 months after the operation was slightly lower than that of in the non-CPM group without a significant difference.…”
Section: Discussionmentioning
confidence: 99%